2021
DOI: 10.3390/ijerph182010744
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of School Attending Adolescents Meeting the Recommended Moderate-to-Vigorous Physical Activity Level and Its Predictors in Lagos, Nigeria

Abstract: We aimed to assess the proportion of school attending adolescents who reached the recommended moderate-to-vigorous physical activity (MVPA) level in Lagos State, Nigeria, as well as the predictors associated with it. A cross-sectional study was conducted among 720 adolescents aged 12–19 years from 20 schools in Lagos State in 2020. MVPA level was assessed using the Activity Questionnaire for Adults and Adolescents. Predictors assessed were socio-demographic variables, anthropometric measurements, sedentary beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“… 27 Recent studies have shown a prevalence of about 5.8%−9.7%. 11 , 28 A continuous increase in the prevalence of overweight could further compound this barrier to physical activity in the future, creating a vicious cycle of both increasing adolescence overweight and decreasing physical activity levels. This calls for targeted interventions of behavioral modifications such as diet and physical activity, which have shown to have moderate quality evidence for the lowering of body weights in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 27 Recent studies have shown a prevalence of about 5.8%−9.7%. 11 , 28 A continuous increase in the prevalence of overweight could further compound this barrier to physical activity in the future, creating a vicious cycle of both increasing adolescence overweight and decreasing physical activity levels. This calls for targeted interventions of behavioral modifications such as diet and physical activity, which have shown to have moderate quality evidence for the lowering of body weights in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence from a narrative review which included data from 1983 to 2013 reported that about 1.0%−8.6% of Nigerian adolescents were overweight 27 . Recent studies have shown a prevalence of about 5.8%−9.7% 11,28 . A continuous increase in the prevalence of overweight could further compound this barrier to physical activity in the future, creating a vicious cycle of both increasing adolescence overweight and decreasing physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations